SCHOOL BULLYING, DITINJAU DARI SUDUT PANDANG HUKUM (DAMPAK DAN PENANGANAN) - Tom Alfa S. Reumi; Winna Amelia A. Senandi (JURNAL PENGABDIAN PAPUA, 2019)
The implementation of science and technology (IPTEKS) in the form of counseling with the title "School Bullying, Judging from a Legal Perspective" was carried out at the School of Hope Papua, taking into account the schools referred and also others school in Sentani district. The purpose of this research and service is to provide understanding to students in order to understand and understand the factors that cause school intimidation and how to overcome school bullying based on Indonesian laws and regulations. The results of this service are that the material provided in the discussion about the Bullying  at School can be well received by students and using indicators receiving good responses and  assistance  given by student when the update is taking place. Through this service, students are expected to become aware of the forms and factors that cause bullying as well as punishments that can be applied to a compilation of someone doing bullying so that this also becomes a prevention effort if for student. Socialization must also be carried out continuously so that it will minimize the handling of bullying that has recently been carried out in the school environment. Keywords: Bullying, school bullying, handling, environment